HEDONISMO E MORALISMO: CONSUMO NA BASE DA PIRÂMIDE - Marcus Wilcox Hemais; Letícia Moreira Casotti; Everardo Pereira Guimarães Rocha (RAE: Revista de Administração de Empresas, 2013)
Economic stability in Brazil has allowed items that were formerly only accessible to the better-off social classes, to be consumed at ¨the bottom of the pyramid¨. This has aroused the interest of both the academic and business world and led to a desire for a better understanding of this phenomenon. Two lines of argument have arisen with distinct perspectives. The first supports a hedonistic approach, which believes that consumption at the base of the pyramid is driven by a wish to reduce poverty, while the other, where a moralistic standpoint is predominant, criticizes this view because it believes that people´s lives can only be improved by including people with less purchasing power in the production processes. One of the aims of this essay is thus to discuss how the literature on consumption at the bottom of the pyramid, shows features of these types of approaches. In addition, it seeks to encourage further studies by setting out a research agenda.